Editorial for the special issue on commercial banking - Christopher Gan (Journal of Risk and Financial Management, 2020)
The existence of financial intermediaries is arguably an artifact of information asymmetry. Beyond simple financial transactions, financial intermediation provides a mechanism for information transmission, which can reduce the degree of information asymmetry and consequently increase market efficiency. During the process of information transmission, the bank is able to provide unique services in the production and exchange of information. Therefore, banks have comparative advantages in information production, transmission, and utilisation. In credit provision, it is possible for lenders to make Type I and Type II errors. These types of errors are associated with whether banks decide to lend money to borrowers with low repayment capacity or risk missing out on potentially profitable lending. However, the recent US subprime loan crisis and previous financial crises (such as the Mexican, Argentinian, Chilean and Asian financial crises) show it is possible that banks can make both good and bad lending decisions. Does this mean that banks have lost their comparative advantages in leveraging information asymmetry? This Special Issue includes contribution in empirical methods in banking such risk and bank performance, capital regulation, bank competition and foreign bank entry, bank regulation on bank performance, and capital adequacy and deposit insurance.
Keywords: 330; banks; risks; capital